How Ownership Structure Influences Firm Performance in Relation to Its Life Cycle - Firdaus, Nur; Kusumastuti, Retno (Universitas Prasetiya Mulya, 2012)
Ownership structure is considered to be the most influential component in corporate govern-ance; it is also closely related to firm performance. The current research analyzes the effect of ownership structure (both insider ownership—board and managerial ownership, blockholder ownership—and institutional ownership concentration—pressure-insensitive and pres-sure-sensitive) on firm performance (industry adjusted return on asset/IAROA) based on its life cycle. Life cycle is incorporated into the research to examine whether the effect of own-ership structure on firm performance differs at each stage of the life cycle. The current re-search uses imbalanced panel data consisting of 695 observations of sample firms from the manufacturing, IT, and multimedia firms during the 2005-2010 period. The results show that: (1) insider ownership has a significantly non-linear influence on IAROA, indicated by a U-shaped curve (2) blockholders have a significantly positive effect on IAROA in firms at the mature stage; on the contrary, the effect is significantly negative in firms at the growth stage (3) institutional ownership concentration has a significantly negative effect on IAROA across the samples and a significantly positive effect on firms at the mature stage, and (4) pressure-insensitive and pressuresensitive institutional ownerships have a positive and sig-nificant effect on IAROA in firms at the mature stage; on the contrary, the effect is negative and significant in firms at the growth stage.